2019
DOI: 10.1108/el-03-2018-0064
|View full text |Cite
|
Sign up to set email alerts
|

An index-based ranking of conferences in a distinctive manner

Abstract: Purpose Bibliometrics is one of the research fields in library and information science that deals with the analysis of academic entities. In this regard, to gauge the productivity and popularity of authors, publication counts and citation counts are common bibliometric measures. Similarly, the significance of a journal is measured using another bibliometric measure, impact factor. However, scarce attention has been paid to find the impact and productivity of conferences using these bibliometric measures. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this regard, different focuses have been made by the researchers including co-citation approaches to find the trending research areas [6] and different sort of ranking algorithms to rank the important research areas [7]. Similarly, researchers also ranked Conferences on the basis of index and other properties [8] and also used other kind of indexes to rank the authors and journals like Ds index [9]. The researchers also proposed solutions for emerging researchers to help them find the useful topics that produce impactful research papers [2].…”
Section: Related Workmentioning
confidence: 99%
“…In this regard, different focuses have been made by the researchers including co-citation approaches to find the trending research areas [6] and different sort of ranking algorithms to rank the important research areas [7]. Similarly, researchers also ranked Conferences on the basis of index and other properties [8] and also used other kind of indexes to rank the authors and journals like Ds index [9]. The researchers also proposed solutions for emerging researchers to help them find the useful topics that produce impactful research papers [2].…”
Section: Related Workmentioning
confidence: 99%
“…The study suggested that the citation counts of papers presented at elite conferences are approximately equal to the citation counts of articles published in journals at a fair level. The significance of conference papers stems from the fact that, in the fast-moving research of the discipline, publishing papers at conferences takes significantly less time than in journals (Farooq, 2019; Freyne et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, few bibliometric studies of conference papers have been conducted, and these have mostly concentrated on the differences in journal articles (Freyne et al , 2010; Wainer et al , 2011) to prove the value of conference papers as ancillary sources of bibliometric data. For instance, studies have explored differences in citation counts between journal articles and conference papers (Freyne et al , 2010), patterns of reproducing conference papers for journal publication (Wainer et al , 2011), patterns of citing references between both types of publications (Wainer and Valle, 2013) and the development of a widely acceptable conference ranking system, compared to journals’ impact factors (Farooq, 2019; Li et al , 2018).…”
Section: Introductionmentioning
confidence: 99%